Действие хлоридного засоления на морфофизиологические признаки генотипов твердой и мягкой пшеницы - Ханышева, М.А.; Гасымова, Ф.И.; Азизов, И.В. (Фактори експериментальної еволюції організмів, 2016)
Aim. The aim of this work was to study the drought tolerance of durum and bread wheat genotypes regionalized in Azerbaijan. Methods. The object of research were 20 varieties of durum and bread wheat. Photosynthetic ability of chloroplasts was determined by the release of oxygen. PS II activity was determined by the release of oxygen in the reaction medium. Results. Revealed relatively stable wheat genotypes to salinity. Conclusions. We have identified more salt-resistant forms, which can grow in weakly saline soils and can be used as initial materials for developing tolerant forms of wheat. Keywords: wheat, genotypes, salinity, chlorophyll, carotenoids, photosystem.